2022
DOI: 10.3390/met12071150
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Analysis of the Influence of Purines on Copper, Steel and Some Other Metals Corrosion

Abstract: Metals stability and corrosion resistance are very important factors that influence the possibility of their applications. In order to study and foresee the behavior of metals during various applications in all kinds of conditions and media, numerous approaches and techniques are developed and applied. Among those techniques, electrochemical measurements nowadays have a dominant role since they are proved to be highly efficient, reliable, fast, relatively low-cost, and easy regarding the preparation and execut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…With the widespread use of metal products other than carbon steel, such as stainless steel, copper and aluminum, the corrosion of these materials in specific environments has become a pressing issue. In addition to research on the corrosion mitigation of carbon steel, recent studies on the corrosion inhibition of organic compounds on other metal materials like stainless steel, copper and aluminum have also garnered attention [88][89][90][91][92].…”
Section: Research On the Corrosion Inhibition Of Organic Compounds On...mentioning
confidence: 99%
“…With the widespread use of metal products other than carbon steel, such as stainless steel, copper and aluminum, the corrosion of these materials in specific environments has become a pressing issue. In addition to research on the corrosion mitigation of carbon steel, recent studies on the corrosion inhibition of organic compounds on other metal materials like stainless steel, copper and aluminum have also garnered attention [88][89][90][91][92].…”
Section: Research On the Corrosion Inhibition Of Organic Compounds On...mentioning
confidence: 99%
“…The formed CuCl, which is not sufficiently protective, and dissolves when it reacts with excess chloride [6][7][8]. The inhibitors can be introduced to the medium or coated on the metal surface to slow down the corrosion process to avoid corrosion in the metal used in such corrosive media, both methods work well [9][10][11][12][13]. Several investigators have reported [5][6][7][8] that organic compounds can act as possible corrosion inhibitors for numerous metals and alloys in various corrosive media.…”
Section: Introductionmentioning
confidence: 99%